2014
DOI: 10.1007/s12024-014-9567-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA and RNA analysis of blood and muscle from bodies with variable postmortem intervals

Abstract: The breakdown of DNA and RNA in decomposing human tissue represents a major obstacle for postmortem forensic molecular analysis. This study investigated the feasibility of performing PCR-based molecular analysis of blood and muscle tissue from 45 autopsy cases with defined postmortem intervals ranging from one to more than 14 days. It was not possible to collect blood from 38 % of the autopsy cases due to severe coagulation and hemolysis, whereas muscle tissue was available for all cases. PCR-amplifiable DNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…We also observed a striking lack of correlation of PMI with RIN in normal skeletal muscle, and to a similar extent the heart, supporting the tissue type-specific nature of RNA degradation. In forensic settings, RNA has been shown to be stable in muscle up to 1week after death [18]. While not addressed in this study, tissue-type specific RNA degradation has also been reported in ocular tissues with avascular structures having better RNA quality than vascularized structures such as the ciliary body [23].…”
Section: Resultsmentioning
confidence: 99%
“…We also observed a striking lack of correlation of PMI with RIN in normal skeletal muscle, and to a similar extent the heart, supporting the tissue type-specific nature of RNA degradation. In forensic settings, RNA has been shown to be stable in muscle up to 1week after death [18]. While not addressed in this study, tissue-type specific RNA degradation has also been reported in ocular tissues with avascular structures having better RNA quality than vascularized structures such as the ciliary body [23].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, many studies used only tumor 6,8 or diseased 11,12,16 tissue, did not access RNA quality in a comparable manner, 7,10,15 nor were measures of outcome statistically quantified. 2,6,7,10 The importance of these previously established, and newly proposed, variables in maximizing human pancreas RNA quality have not been evaluated alone or in combination with one another. Therefore, this study was performed to identify predictors that increase the odds of obtaining high quality human pancreatic RNA in samples made available through the Network for Pancreatic Organ Donors with Diabetes (nPOD) program.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately neither sample type could be obtained from badly decomposed or charred bodies. In such cases, alternative biological samples such as muscle [22], liver [2], brain tissue [31] or a fragment of the femoral head [32,33] would need to be obtained as a DNA sample. Additionally, further research will need to be conducted in order to determine if the EasiCollect device will be effective in collecting buccal DNA samples from individuals with extraneous substances in their oral cavities.…”
Section: Methods Ofmentioning
confidence: 99%
“…Although blood was previously regarded as the standard specimen for the collection of DNA samples within the ISSN: 2330-0396 mortuary, Hansen et al found that it is not always the best specimen for use in this setting due to the potential presence of coagulation and haemolysis which may inhibit sample collection [22]. Additional issues arise with the collection of this sample type in South African mortuaries due to the lack of a pre-packaged, sterile and quality controlled kit for sample collection.…”
Section: Introductionmentioning
confidence: 99%